Réponses

Meilleure réponse !
2014-02-23T23:07:19+01:00
Bonsoir,

A)  (5x - 1)² + 10x - 2 = (5x - 1)² + 2(5x - 1)
                               = (5x - 1)(5x - 1) + 2(5x - 1)
                               = (5x - 1)[(5x - 1) + 2]
                               = (5x - 1)(5x - 1 + 2)
                               = (5x - 1)(5x + 1)

B)  9x + 6 - (3x + 2)² = 3(3x + 2) - (3x + 2)²
                               = 3(3x + 2) - (3x + 2)(3x + 2)
                               = (3x + 2)[3 - (3x + 2)]
                               = (3x + 2)(3 - 3x - 2)
                               = (3x + 2)(1 - 3x)

C) (2x + 5)(2 - x) - 2 + x = (2x + 5)(2 - x) - (2 - x)
                                   = (2x + 5)(2 - x) - 1 *(2 - x)
                                   = (2 - x)[(2x + 5) - 1]
                                   = (2 - x)(2x + 5 - 1)
                                   = (2 - x)(2x + 4)

D)  x(x + 2) - x - 2 = x(x + 2) - (x + 2) 
                           = x(x + 2) - 1*(x + 2)
                           = (x + 2)(x - 1)